Systemy parlamentarne wybranych państw arabskich i muzułmańskich w świetle notatki dla kierownictwa MSZ z 1972 r. - Knopek, Jacek (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The paper discusses the parliamentary systems of selected Arab and Muslim countries in the Middle East and North Africa at the turn of the 1960s.The analysis concerns a document drawn up for executives in the Ministry of Foreign Affairs in late 1972, with an attachment discussing the parliamentary systems of the countries of primary importance for the goals and interests of Poland. As concerns the Middle East, the parliamentary systems of Lebanon, Syria, Jordan, Iraq, Kuwait, Iran and North and South Yemen were described. In North Africa, the analysis encompassed the Maghreb region: Morocco, Algeria, Tunisia, and the Mashrek region: Egypt, Libya and Sudan. The paper concludes with a statement that the document was an accurate and faithful presentation of the parliamentary systems of representative states. Political relations in this region were developing dynamically at that time, military coups and coups d’état occurred, some states were leaning towards socialism, while maintaining their family or religious structures, while others were only just gaining their full sovereignty and in- dependence. The situation of Israel continued to be complicated, as the state remained highly confrontational towards Arab countries. This last issue was the reason for Poland’s failing to achieve the strategic goals of its foreign policy in the Middle East and North Africa. Another Israeli-Arab war in October 1973 made Polish decision makers realize how fragile the foundations of states in the region were, preventing Poland from becoming fully involved in Arab and Muslim countries.
Parliamentary systems of selected Arab and Muslim states as presented in a memo for executives in the Ministry of Foreign Affairs in 1972
Keywords: systemy polityczne; parlamenty; kraje arabskie i muzułmańskie; polska polityka zagraniczna